The effectiveness of blended learning scientific writing training in the condition of multitasking participants - Sevrien Erwina Arumbayati; Endan Suwandana; Eni Lestariningsih (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2022)
The purpose of this study was to examine a learning phenomenon that emerged during the hectic distance learning method (online), namely the multitasking phenomenon carried out by trainees. This research is interesting because currently multitasking is an obstacle as well as a challenge faced by every online training participant. The question to be answered is whether the training are effective, when participants are doing multitasking. This research was conducted on participants of the Scientific Writing Training (KTI) at the Central Statistics Agency's Education and Training Center in 2021 and 2022. The method used in this study was descriptive quantitative analysis. The results of this study show that the participation of the trainees as indicated by their virtual attendance and their focus/concentration is disrupted by the large number of workloads (multitasking). However, the participants' multitasking conditions did not affect the effectiveness of the training as indicated by the increase in the post-test scores from the pre-test scores and the completion of the paper manuscript assignment. Nevertheless, the training organizers and the leaders of the trainees still need to consider this fact to take actions to reduce multitasking tension so as to increase the level of attendance and focus/concentration of the trainees.